Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Wimart-Rousseau, Cathy; Wagener, Thibaut; Álvarez, Marta; Moutin, Thierry; Fourrier, Marine; Coppola, Laurent; Niclas-Chirurgien, Laure; Raimbault, Patrick; D’Ortenzio, Fabrizio; Durrieu de Madron, Xavier; Taillandier, Vincent; Dumas, Franck; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (AT), total dissolved inorganic carbon (CT), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of AT variation vs. CT variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of CT by autotrophic processes. The high range of AT variations, combined to temperature changes, has a strong impact on the variability of the seawater pCO2 (pCO2SW). Based on Argo float data, an entire annual cycle for pCO2SW in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO2. By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pHT25 of −0.0024 ± 0.0004 pHT25 units.a–1. The changes in the carbonate system are driven by the increase of atmospheric CO2 but also by unexplained temporal changes in the surface AT content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.